2016
DOI: 10.1074/jbc.m115.708131
|View full text |Cite
|
Sign up to set email alerts
|

Activated α2-Macroglobulin Regulates Transcriptional Activation of c-MYC Target Genes through Cell Surface GRP78 Protein

Abstract: Activated ␣ 2 -macroglobulin (␣ 2 M*) signals predominantly through cell surface GRP78 (CS-GRP78) to promote proliferation and survival of cancer cells; however, the molecular mechanism remains obscure. c-MYC is an essential transcriptional regulator that controls cell proliferation. We hypothesize that ␣ 2 M*/CS-GRP78-evoked key signaling events are required for transcriptional activation of c-MYC target genes. Activation of CS-GRP78 by ␣ 2 M* requires ligation of the GRP78 primary amino acid sequence (Leu 98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 48 publications
2
53
0
Order By: Relevance
“…Thus, relocalization of stress-inducible ER and cytosolic chaperones to the cell surface could represent a major common adaptive mechanism for cells to expand the functionality of these proteins in response to proteotoxic stress, turning on signaling pathways distinct from their intracellular functions and thereby impacting both survival and death. This is particularly important in the context of cancer where cell-surface ER chaperones have been reported to regulate oncogenic signaling pathways, proliferation, cell adhesion, and immunity (4,6,9).…”
mentioning
confidence: 99%
“…Thus, relocalization of stress-inducible ER and cytosolic chaperones to the cell surface could represent a major common adaptive mechanism for cells to expand the functionality of these proteins in response to proteotoxic stress, turning on signaling pathways distinct from their intracellular functions and thereby impacting both survival and death. This is particularly important in the context of cancer where cell-surface ER chaperones have been reported to regulate oncogenic signaling pathways, proliferation, cell adhesion, and immunity (4,6,9).…”
mentioning
confidence: 99%
“…4D). We focus on A2M not only because it is expressed in CD9 + cells at high levels, but also because activation of A2M signals was reported to promote proliferation and survival of cancer cells [44]. We also con rmed the high expression of A2M protein in CD9 + cells of THP-1 and HL-60 by Western blotting (Fig.…”
Section: A2m Is Expressed In Cd9 + Cells At High Levelsmentioning
confidence: 90%
“…In addition, these cytokines induce the production of various acute‐phase proteins and these proteins which are contained in the serum globulin fraction 24, 25, 26, 27, 28. Interestingly, it has been reported that these cytokines and acute‐phase proteins are associated with the prognosis of cancer patients 29, 30, 31, 32, 33, 34, 35, 36, 37. These facts suggest that an elevated serum globulin level may reflect an enhancement of tumor progression and distant metastasis due to an alteration of tumor cell biology and suppression of antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%